2020
DOI: 10.11648/j.cajph.20200605.16
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Determinants of Etiologies and Complications of Chronic Liver Diseases Among Patients at a Tertiary Hospital in a Lower Economic Region of Ghana

Abstract: There is dearth of data on the epidemiology of chronic liver diseases (CLDs) in northern Ghana. To this extent, we intended to investigate the distribution and determinants of the etiologies and complications of CLDs at the Tamale Teaching Hospital, a referral hospital of northern Ghana. The medical records of patients with CLDs admitted at the medical ward of Tamale Teaching Hospital from June to December 2019 were reviewed in a retrospective cross-sectional study. Out of 180 patients reviewed, 130 (72.2%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…The number of CLD patients with ALD was significantly higher than those diagnosed with CVH. This is at variance with studies which found chronic viral hepatitis B to be the most common cause of CLD (29)(30)(31) . The higher prevalence of ALD in this study was probably due to the high rate of alcohol consumption (locally brewed gin called 'ogogoro' or 'kai-kai') in our region (32) .…”
Section: Discussioncontrasting
confidence: 84%
“…The number of CLD patients with ALD was significantly higher than those diagnosed with CVH. This is at variance with studies which found chronic viral hepatitis B to be the most common cause of CLD (29)(30)(31) . The higher prevalence of ALD in this study was probably due to the high rate of alcohol consumption (locally brewed gin called 'ogogoro' or 'kai-kai') in our region (32) .…”
Section: Discussioncontrasting
confidence: 84%
“…These findings showed that cisplatin has a considerable cytotoxic effect on the proliferation of HepG-2 cells. Furthermore, morphological variations were seen in HepG-2 cells treated with cisplatin, as shown in Figures (2) and (3), when compared to doxorubicin and DMSO, after treatment for 48 hours with 1.56 to 12.5 μg of doxorubicin did not cause notable changes in morphology or cell number. Furthermore, treatment with 25-50 μg of cisplatin resulted in significant morphological alterations and notably suppression.…”
Section: Morphological Changes and Cell Proliferation Inhibition Of Hepg-2 Cells By Cisplatin And Doxorubicinmentioning
confidence: 84%
“…Hepatocellular carcinoma is the most prevalent form of primary liver cancer [1]. Hepatocellular carcinoma is generally always found in people with chronic liver disorders, such as cirrhosis-related hepatitis B or C infection [2]. Patients with chronic liver illness are more likely to develop hepatocellular carcinoma, the most common kind of liver cancer.…”
Section: Introductionmentioning
confidence: 99%